3D diffraction imaging of linear features and its application to seismic monitoring. (26th August 2013) - Alonaizi, Faisal; Pevzner, Roman; Bóna, Andrej; Shulakova, Valeriya; Gurevich, Boris
ABSTRACT Many subsurface features, such as faults, fractures, cracks, or fluid content terminations are defined by geological discontinuities. The seismic response from such features is encoded in diffractions. We develop an algorithm for imaging such discontinuities by detecting edge diffractions. The algorithm exploits phase‐reversal phenomena of edge diffractions and uses them as a criterion to separate these diffractions from specular reflections and diffractions produced by a leaner object. The performance of the method is demonstrated on both synthetic and real 3D seismic data. The output image focuses the diffracted energy back to its origin and shows high semblance values at the edge of the object. The method is applied on conventionally stacked data producing an image that contains only diffraction events called the D‐volume. We also reveal the potential of diffractions to image and track the changes of a CO2 plume using time‐lapse analysis and detect any possible CO2 seepage from its primary containment.